Genetic variability and correlation studies for growth and yield characters in chilli (Capsicum annuum L.) - V Kumar, S Thakur, K Amit, I Ahad, (Journal of Spices and Aromatic Crops, 2017)
Twenty three genotypes were used to study the genetic variability, heritability, genetic advance and correlation for growth and yield contributing characters in chilli under Kashmir conditions. Significant variations were observed for all the characters studied except for days to flowering and crop duration [mature (green) as well as dry (red)]. High Phenotypic Coefficient Variation (PCV) and Genotypic Coefficient Variation (GCV) were recorded for number of fruits plant-1, fruit weight and dry (red) yield. All the characters showed high heritability estimates. However, number of the fruits plant-1, green fruit yield plant-1, dry (red) yield plant-1, number of seeds plant-1 and plant height exhibited high genetic advance as percentage of mean indicating additive gene effect. Fruit yield (green and red) plant-1 was positively and significantly correlated with number of fruits plant-1 and fruit length. It revealed that the characters viz., plant height, fruit length, number of fruits plant-1, fruit weight and fruit yield (green & red) are the most important traits for genetic improvement of chilli.